The correlation of CBCT analysis derived bone density parameters with primary implant stability – a clinical study - Mikić, Mirko; Vlahović, Zoran; Nenezić, Dragoslav; Videnović, Goran; Ilić, Danijela; Mladenović, Raša (Vojnosanitetski pregled, 2021)
Background/Aim. There are numerous studies on the usefulness of computed tomography (CT) in the assessment of the bone volume and morphology and on the relationship between CT and primary implant stability. But there is the scarcity of data about the correlation between bone density and the value of primary implant stability. The aim of this study was to examine the correlation of cone beam CT (CBCT) analysis derived bone density with primary stability value. Methods. Clinical prospective experimental study was conducted on 38 healthy patients missing one tooth in the lateral region. It was planned to install Bredent Blue Sky Narrow self-taping dental implants with dimensions 3.5 × 10 mm. During preoperative preparation, a CBCT scan was performed on Planmeca apparatus, followed by preimplantation measurements and planning in the CBCT apparatus software (Romexis). The mean value of the average bone density was automatically generated and expressed in Hounsfield units (HU). Upon implant placement, we performed measurements of the primary implant stability using Osstell apparatus. Results. Of the 38 patients included in the study, there were 68.4% male patients and 31.6% female patients. The arithmetic mean of the measured bone density of all subjects in the study amounted to 536.2 HU. The arithmetic mean of dental implant primary stability for all subjects in the study was 68.7 ISQ. There was a statistically significant strong positive connection between HU and ISQ (r = 0.744, p < 0.001). Higher HU values were connected to higher ISQ values. In the multivariate linear regression model, statistically significant predictors of higher ISQ values: males (B = 4.669; p = 0.047) and higher HU values (B = 0.032; p < 0.001). Conclusion. In our clinical study, there was a statistically significant strong positive correlation between the bone density expressed in HU units, measured in the software of the CBCT device and the primary stability of dental implants expressed in ISQ units.